The Concept of Personality of Islamic Religious Education Teachers based on Kuntowijoyo’s Prophetic Social Science - Nadlir Nadlir; Sibawaihi Sibawaihi; Sabarudin Sabarudin; Diah Rusmala Dewi (UIN Sunan Ampel Surabaya, 2022)
Teachers’ competence has been discussed by some Islamic figures as the main indicator in order to formulate the concept of teachers’ personality for teachers in general. However, the indicators that are spesifically for Islamic education teachers have not been discussed yet, so it is important to deepen and specify the study to formulate criteria of the concept of teachers’ personality that mainly focus on Islamic education teachers based on Islamic view. Based on those reasons, the writers are interested in conducting research in the area of the concept of teachers’ personality based on the Kuntowijoyo’s prophetic social science which contains transcendence, humanzation and liberation values. The prophetic social science by kuntowijoyo is formulated based on the surah Ali Imron verse 110. In this research, the writers will focus on the teachers of Islamic religious education (PAI). By using the concept, the research is expected to formulate the indicators for the concept of teachers’ personality which is intended specifically for Islamic religious education teachers. This research uses library research methodology with psychological-pedagogical approach. The main source of the research is the book by Kuntowijoyo with some secondary data sources. The results of the study show that: (1) the concept of teacher’s personality, in the perspective of Islamic education, must refer to the noble morals as exemplified by the Prophet Muhammad SAW based on the values of Islamic teachings. (2) the concept of Islamic education teacher’s personality based on Kuntowijoyo’s prophetic social science must include three prophetic values (transcendence, humanist and liberating). So, in order to acquiring the concept of teachers’ personality, it is important for the Islamic education teachers to be transcendence, liberating and humanist as well as emulating the values of Prophet Muhammad. In relation to the current context, this concept can be used as a solution in response to the challenges of Islamic religious education teachers that come from the aspect of the teacher's personality. So, it is hoped that the indicators which is based on kuntowijoyo’s prophetic social science can be used as the formulation for all teachers to upgrade their personality competence, especially for Islamic religious education teachers.